2018
DOI: 10.1111/jpn.13022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacillus subtilis C‐3102 on production, hatching performance, egg quality, serum antioxidant capacity and immune response of laying breeders

Abstract: To investigate the supplemental effects of Bacillus subtilis C‐3102 on the production, hatching performance, egg quality, serum antioxidant capacity and immune response of laying breeders, a total of 480 Xuefeng black‐bone (25‐week‐old) hens were randomly assigned into four treatment groups: Hens fed the basal diets with 0 (CON), 3.0 × 105 (BS‐1), 6.0 × 105 cfu/g (BS‐2) and 9.0 × 105 (BS‐3) cfu/g of B. subtilis C‐3102. As the B. subtilis C‐3102 level increased, egg weight (linear, p < 0.01; quadratic, p = 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 50 publications
(62 reference statements)
2
30
3
1
Order By: Relevance
“…Therefore, we assumed that BSEO have no significant effect on ovomucin content, and may be beneficial in extending the shelf life of the eggs via improving yolk index, this finding was similar to our previous study with result that dietary BS linearly increased yolk index (Liu et al 2019). Unexpectedly, the supplementation of BSEO decreased eggshell thickness in a linear manner, which was contrary to the result of most researches (Abdel-Wareth 2016; Liu et al 2019). And, the value of eggshell strength decreased with an increased BSEO supplementation.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Therefore, we assumed that BSEO have no significant effect on ovomucin content, and may be beneficial in extending the shelf life of the eggs via improving yolk index, this finding was similar to our previous study with result that dietary BS linearly increased yolk index (Liu et al 2019). Unexpectedly, the supplementation of BSEO decreased eggshell thickness in a linear manner, which was contrary to the result of most researches (Abdel-Wareth 2016; Liu et al 2019). And, the value of eggshell strength decreased with an increased BSEO supplementation.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, a noteworthy improvement of the activities oxidative stress and immune response in chicken (Abramowicz et al 2019;Abudabos et al 2019;Park et al 2020), duck (Zhang et al 2016), and quail (Abdel-Moneim et al 2020) has been demonstrated. Furthermore, our previous studies also found that dietary supplementation of 9.0 Â 10 5 CFU/g BS effectively increased egg weight, fertility and hatchability, and improved egg quality in laying hens (Liu et al 2019).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations